Nutritional Formulation for Patients with Angelman Syndrome: A Randomized, Double-Blind, Placebo-Controlled Study of Exogenous Ketones. Issue 12 (11th September 2021) - Carson, Robert P; Herber, Donna L; Pan, Zhaoxing; Phibbs, Fenna; Key, Alexandra P; Gouelle, Arnaud; Ergish, Patience; Armour, Eric A; Patel, Shital; Duis, Jessica
ABSTRACT: Background: Angelman syndrome (AS) patients often respond to low glycemic index therapy to manage refractory seizures. These diets significantly affect quality of life and are challenging to implement. These formulations may have benefits in AS even in the absence of biomarkers suggesting ketosis. Objectives: We aimed to compare an exogenous medical food ketone formulation (KF) with placebo for the dietary management of AS. Methods: This randomized, double-blind, placebo-controlled, crossover clinical trial was conducted in an academic center from 15 November, 2018 to 6 January, 2020. Thirteen participants with molecularly confirmed AS aged 4–11 y met the criteria and completed the 16-wk study. The study consisted of four 4-wk phases: a baseline phase, a blinded KF or placebo phase, a washout phase, and the crossover phase with alternate blinded KF or placebo. Primary outcomes were safety and tolerability rated by retention in the study and adherence to the formulation. Additional secondary outcomes of safety in this nonverbal population included blood chemistry, gastrointestinal health, seizure burden, cortical irritability, cognition, mobility, sleep, and developmental staging. Results: Data were compared between the baseline, KF, and placebo epochs. One participant exited the trial owing to difficulty consuming the formulation. Adverse events included an increase in cholesterol in 1 subject when consuming KF and a decrease in albumin in 1 subject when consuming placebo. Stool consistency improved with KF consumption, from 6.04 ± 1.61 at baseline and 6.35 ± 1.55 during placebo to 4.54 ± 1.19 during KF ( P = 0.0027). Electroencephalograph trends showed a decrease in Δ frequency power during the KF arm and event-related potentials suggested a change in the frontal memory response. Vineland-3 showed improved fine motor skills in the KF arm. Conclusions: The exogenous KF appears safe. More data are needed to determine the utility of exogenous ketones as a nutritional approach in children with AS. This trial was registered at clinicaltrials.gov as NCT03644693.